Utopian Gossip: “The Homosexual in Society” from Robert Duncan to New Narrative - Eric Sneathen (Sillages Critiques)
This paper collects the commentary surrounding Robert Duncan’s 1944 essay “The Homosexual in Society” to develop an account of Duncan’s relationship to New Narrative, a group of younger, mostly-gay poets. The first half of the essay focuses directly on Duncan’s composition of the essay, his emendations of 1959, his experiences with the editor John Crowe Ransom, and Duncan’s portions of interviews with gay poets throughout the 1970s that brought out new details about “The Homosexual in Society” essay. The second half of the essay considers how New Narrative writers related to Duncan and his essay, including a shared interest in gossip. Drawing on the totality of this archive, the essay suggests two new themes that can be drawn from “The Homosexual in Society” for contemporary readers: the (in)commensurability of race and sexuality and the rejection of homo-fascism.